Spiral staircase at David Sassoon Clock Tower - Ghosh, Ayan (2023)
The apparatus is installed on the upper floor of the clock tower. A wrought iron spiral staircase leads to the upper level of the clock tower. Access to this staircase is now prohibited, and no one can climb up.